Analisis Daya Dukung Wisata dan Strategi Pengembangan Objek Wisata Celosia Happy & Fun Desa Candi, Kabupaten Semarang - Sugiarti, Putri Ayu; Arifien, Moch. (Geo-Image, 2021)
The tourism in Candi Village, Semarang District has great potential to be developed. The existence of Celosia Happy & Fun attraction is one of the efforts to exploit that potential. To avoid tourism management that exceeds its capacity, it is necessary to know how much the carrying capacity of the tourism object is. The purpose of this study are 1. To determine the carrying capacity of Celosia Happy & Fun, 2. To determine the perceptions of tourists towards Celosia Happy & Fun attractions, 3. To determine Celosia Happy & Fun tourism development strategy. Data analysis uses quantitative description, calculation the value of tourism carrying capacity based on Cifuentez (1992) in (Muta'ali, 2015) and SWOT analysis. The results of this research showed that the value of the carrying capacity of tourism in Celosia Happy & Fun tourist attraction was in the large category, with an effective carrying capacity is 343 tourists / day and an average real tourist visit is 241 tourists / day, meaning that the carrying capacity of tourism was large and can be developed. From the results of the research, it is known that 96% of tourists were satisfied and 4% of tourists were very satisfied to have carried out tourism activities in Celosia Happy & Fun attraction. Based on the SWOT analysis the main strategy for developing Celosia Happy & Fun is a strategy that uses strength to take advantage of the opportunities. Sektor pariwisata di Desa Candi, Kabupaten Semarang memiliki potensi yang besar untuk dikembangkan. Beroperasinya objek wisata Celosia Happy & Fun adalah salah satu upaya untuk memanfaatkan potensi tersebut. Untuk menghindari pengelolaan pariwisata yang melebihi kapasitasnya maka perlu diketahui berapa nilai daya dukung wisata dari objek wisata tersebut. Tujuan dari penelitian ini adalah 1. Mengetahui nilai daya dukung wisata Celosia Happy & Fun, 2. Mengetahui persepsi wisatawan terhadap objek wisata Celosia Happy & Fun, 3. Mengetahui strategi pengembangan objek wisata Celosia Happy & Fun. Analisis data menggunakan deskriptif kuantitatif, perhitungan nilai daya dukungwisata berdasarkan Cifuentez (1992) dalam (Muta’ali, 2015), dan analisis SWOT. Hasil dari penelitian diketahui bahwa nilai daya dukung efektif sebesar 343 wisatawan/hari dan rata-rata kunjungan riil wisatawan sebesar 241 wisatawan/hari, artinya daya dukung wisata besar dan masih dapat dikembangkan. Dari hasil penelitian, diketahui bahwa 96% wisatawan merasa puas dan 4% wisatawan merasa sangat puas telah melakukan aktivitas pariwisata di objek wisata Celosia Happy & Fun. Berdasarkan analisis SWOT strategi pengembangan objek wisata Celosia Happy & Fun utama adalah strategi yang menggunakan kekuatan untuk memanfaatkan peluang.